Optimalisasi Pemahaman Fisika Pada Hukum Newton Dengan Inquiry - Heuristik Vee Berbantuan Alat Peraga - Nurin fitriana (JURNAL PENDIDIKAN SAINS UNIVERSITAS MUHAMMADIYAH SEMARANG, 2020)
This study aims to improve the optimization of students in the ability to construct their knowledge in understanding the concepts of Basic Physics in particular Newton's Law with Inquiry-Heuristic Assisted Vee Aids. The type of research used in this study is the type of explanatory research and analysis used in this study using SPSS, Descriptive Interpretation, Pearson Correlation Interpretation, linear regression, ANOVA. The results showed that the Pearson correlation test showed a value of 0.666 shows a positive correlation between the ability of knowledge construction with learning outcomes. Analysis of the coefficient of determination is 0.444, which means that the influence of the ability of knowledge construction to learning outcomes is 44.4% with F value = 18,339. The regression model can be used to predict the participation variable. Thus it is stated that the ability of knowledge construction has a strong degree of closeness to learning outcomes.